Genetic resources and breeding approaches for improvement of amaranth (Amaranthus spp.) and quinoa (Chenopodium quinoa) - Anuradha,; Kumari, Manisha; Zinta, Gaurav; Chauhan, Ramesh; Kumar, Ashok; Singh, Sanatsujat; Singh, Satbeer (Frontiers in Nutrition, 2023)
Nowadays, the human population is more concerned about their diet and very specific in choosing their food sources to ensure a healthy lifestyle and avoid diseases. So people are shifting to more smart nutritious food choices other than regular cereals and staple foods they have been eating for a long time. Pseudocereals, especially, amaranth and quinoa, are important alternatives to traditional cereals due to comparatively higher nutrition, essential minerals, amino acids, and zero gluten. Both Amaranchaceae crops are low-input demanding and hardy plants tolerant to stress, drought, and salinity conditions. Thus, these crops may benefit developing countries that follow subsistence agriculture and have limited farming resources. However, these are underutilized orphan crops, and the efforts to improve them by reducing their saponin content remain ignored for a long time. Furthermore, these crops have very rich variability, but the progress of their genetic gain for getting high-yielding genotypes is slow. Realizing problems in traditional cereals and opting for crop diversification to tackle climate change, research should be focused on the genetic improvement for low saponin, nutritionally rich, tolerant to biotic and abiotic stresses, location-specific photoperiod, and high yielding varietal development of amaranth and quinoa to expand their commercial cultivation. The latest technologies that can accelerate the breeding to improve yield and quality in these crops are much behind and slower than the already established major crops of the world. We could learn from past mistakes and utilize the latest trends such as CRISPR/Cas, TILLING, and RNA interference (RNAi) technology to improve these pseudocereals genetically. Hence, the study reviewed important nutrition quality traits, morphological descriptors, their breeding behavior, available genetic resources, and breeding approaches for these crops to shed light on future breeding strategies to develop superior genotypes.